Cryopreserving 3D cell culture models of Alzheimer’s disease in hydrogel microbeads - Jae Jung Kim; Matthias Hebisch; Sang Su Kwak; Monica Zheng; Shreya Nuli; Jun-Seok Bae; Emma Brand; Rudolph E. Tanzi; Daniel Irimia; Doo Yeon Kim (Scientific Reports)
Abstract Long-term preservation of fully differentiated human neurons poses a longstanding challenge in neuroscience research. Numerous cellular disease models have been established using cultured human neuronal cells, including our three-dimensional (3D) human neural cell culture model of Alzheimer’s disease (AD). However, the absence of a reliable method for preserving fully differentiated human neural cell cultures for a long time has hindered the sharing and standardization of these models. To address this critical limitation, we focused on cryopreservation, which is the gold standard for long-term preservation, and combined this with three key technological advancements. First, we employed parallelized microfluidic devices for the efficient generation of 3D cell cultures within uniform hydrogel microbeads (~ 220 μm), which facilitate the rapid exchange of media ingredients and cryoprotectants. Second, we implemented a cytophobic microwell system to safeguard neuron-encapsulated microbeads from fusion and aggregation. Third, we developed a novel inducible AD cell model optimized for cryopreservation and AD drug testing. We have successfully maintained encapsulated control and AD neural progenitor cells in microwells during differentiation for 12 days. Notably, fully differentiated human neural cells can be cryopreserved within Matrigel microbeads while retaining intact and mature neuronal processes, exhibiting no signs of damage to neurites following freeze/thaw cycles. Furthermore, we have demonstrated the successful cryopreservation, thawing, and induction of pathogenic Amyloid-β 42 (Aβ42) generation in fully differentiated AD neural progenitor cells. Our study offers a solution for one of the major challenges in neuroscience research, utilizing porous hydrogel microbead structures to facilitate rapid delivery of cryoprotectants and protect complex neuronal structures without undergoing damaging cell dissociation steps. The inducible "3D human microbead model of AD" enhances the speed, efficacy, and reproducibility of AD drug screening.